Point prevalence survey of antibiotics in a pediatric tertiary hospital in the Republic of Panama - Ximena Norero; Dora Estripeaut; Elizabeth Castaño; Jacqueline Levy; Paola Lichtenberger; José Pablo Díaz-Madriz; José Luis Bustos; Robin Rojas Cortés; Gabriel Levy-Hara (Revista Panamericana de Salud Pública)
Objective. To conduct a point prevalence survey (PPS) of antibiotic use in the main pediatric tertiary-level hospital in Panama City to establish antibiotic prevalence and identify key areas for addressing antimicrobial resistance. Methods. This point prevalence survey (PPS) conducted in a tertiary-level hospital in Panama followed the Pan American Health Organization’s adaptation of the methodology proposed by the World Health Organization for PPSs on antibiotic use. Information obtained included patients’ demographic characteristics, antimicrobial prescriptions, indication for antimicrobial use, and prescription’s adherence to guidelines. Results. Of 298 patients surveyed from August to September 2023, 176 (59.0%) were treated with antibiotics. The pediatric ward (86.3%) and the neonatal intensive unit (80.0%) had the highest prevalence of antibiotic use. Hospital-acquired infections accounted for 32.6% of antibiotic prescriptions, with piperacillin/tazobactam (29.4%), meropenem (15.3%), amikacin (15.3%), and ampicillin/sulbactam (10.2%) being the most prescribed. Treatment for community-acquired infections represented 55.9% of antibiotic prescriptions, with ampicillin (24.6%), gentamicin (22.6%), and ampicillin/sulbactam (14.0%) being the most frequently used. Of the prescriptions considered in the analysis, 61.0% adhered to hospital guidelines. Conclusions. This PPS observed a high prevalence of antibiotic use. The findings suggest it is necessary to assess the need for ampicillin, gentamicin, and piperacillin-tazobactam use in patients admitted to pediatric critical care units, with special emphasis on children with pneumonia and sepsis diagnosis, the most common pathologies for which an antimicrobial was prescribed.